A Comparative Study on the Pharmacognostical, Phytochemical And Physico-Chemical Studies of Solanum Melongena L., Solanum Xanthocarpum L. and Solanum Trilobatum L. (Solanaceae) - Dahanayake, J.M.; Perera, P.K.; Galappaththy, P.; Arawwawala, L.D.A.M. (European Journal of Pharmaceutical and Medical Research, 2024)
The plant species of the family Solanaceae contain trees, shrubs and herbs with natural compounds. The Solanum genus of this family accommodates diverse groups of flowering plants, which include medicinal plants and food crops. Among medicinal plants, Solanum melongena L., Solanum xanthocarpum L. and Solanum trilobatum L. are commonly used in the Sri Lankan traditional and Ayurveda system of medicine. These three medicinal plants have demonstrated strong efficacy against diseases, especially in respiratory system due to their pharmacologically active secondary metabolites. No chemical and pharmacognostical comparison have been done for Sri Lankan grown species of these three plants. Hence the main objective of this study was to compare the physicochemical, phytochemical and pharmacognostical profiles of S. melongena, S. xanthocarpum and S. trilobatum L. to standardize the three plant materials. Pharmacognostical characters and quality control parameters of ash values, extractive values, heavy metals and qualitative phytochemical analysis were performed according to WHO guidelines. Further analysis of TLC and HPTLC fingerprint patterns of methanolic extract of these plants was also conducted. The results of ash values and extractable values were comparable with the results in Ayurveda pharmacopeia of India and water-soluble ash content of S. xanthocarpum (6.4 %) is higher than the S. melongena (2.8 %) and S. trilobatum (4.3 %). The hot water and hot methanol extractable matter of S. xanthocarpum plant is higher (23.8%, 20.4%) than the S. melongena (8.8%, 9.7%) and S. trilobatum (13.8%, 7.4%) respectively. Phytochemical analysis reveals the presence of saponins, alkaloids, tannins, phenols, flavanoids, terpinoids, cardiac glycosides and steroids. Results of these physico-chemical, phytochemical, pharmacognostical and TLC analysis can be used to compare the specific features among these three species, assess the quality and detection of any adulteration for S. melongena, S. xanthocarpum and S. trilobatum
Keywords: Solanaceae; Pharmacognosy; Physicochemical analysis; Phytochemicals